Human Mature Adipocytes Express Albumin and This Expression Is Not Regulated by Inflammation - Maria Luisa Sirico; Bruna Guida; Alfredo Procino; Andrea Pota; Maurizio Sodo; Giuseppe Grandaliano; Simona Simone; Giovanni Pertosa; Eleonora Riccio; Bruno Memoli (Mediators of Inflammation)
Aims. Our group investigated albumin gene expression in human adipocytes, its regulation by inflammation and the possible contribution of adipose tissue to albumin circulating levels. Methods. Both inflamed and healthy subjects provided adipose tissue samples. RT-PCR, Real-Time PCR, and Western Blot analysis on homogenates of adipocytes and pre-adipocytes were performed. In sixty-three healthy subjects and fifty-four micro-inflamed end stage renal disease (ESRD) patients circulating levels of albumin were measured by nephelometry; all subjects were also evaluated for body composition, calculated from bioelectrical measurements and an thropometric data. Results. A clear gene expression of albumin was showed in pre-adipocytes and, for the first time, in mature adipocytes. Albumin gene expression resulted significantly higher in pre-adipocytes than in adipocytes. No significant difference in albumin gene expression was showed between healthy controls and inflamed patients. A significant negative correlation was observed between albumin levels and fat mass in both healthy subjects and inflamed ESRD patients. Conclusions. In the present study we found first time evidence that human adipocytes express albumin. Our results also showed that systemic inflammation does not modulate albumin gene expression. The negative correlation between albumin and fat mass seems to exclude a significant contributing role of adipocyte in plasma albumin.